Manejo integrado de Cydia pomonella (L) en la producción de manzana roja, Malus domestica Borkh - Toaza Jurado, Zurica Sabrina (2024)
The integrated management of Cydia pomonella in the production of red apples Malus Domestica Borkh is crucial for agriculture due to the serious damage that this pest can cause in apple crops. Protecting crops from the harmful effects of this pest represents a significant challenge for producers, since determining its presence is essential to implement effective control measures. This study is based on the collection and analysis of various sources of information to evaluate the effectiveness of the implemented control strategies. The findings highlight the importance of monitoring the adult moth population using synthetic sex pheromone traps, which allows estimating key moments in the pest's life cycle and determining the best time to apply control measures. Several authors have highlighted the effectiveness of integrated pest management (IPM) in controlling codling moth, suggesting a promising approach to protect the quality and productivity of fruit crops. In conclusion, comprehensively addressing the codling moth problem is crucial, and it is necessary to continue developing and improving control strategies. The implementation of a regular monitoring program and the promotion of sustainable pest control practices aimed at protecting apple crops from the damaging effects of the codling moth is recommended. It is essential to ensure the safety and productivity of fruit crops in the future.